2021
DOI: 10.48550/arxiv.2111.10260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The slope, the hill, the drop, and the swoosh: Learning about the nuclear matter equation of state from the binary Love relations

Hung Tan,
Veronica Dexheimer,
Jacquelyn Noronha-Hostler
et al.

Abstract: Analyses that connect astrophysical observations of neutron stars with nuclear matter properties sometimes rely on equation-of-state insensitive relations. We show that the slope of the binary Love relations (i.e. between the tidal deformabilities of binary neutron stars) encodes the rate of change of the nuclear matter speed of sound below three times nuclear saturation density. Twin stars lead to relations that present a signature "hill," "drop," and "swoosh" due to the second (mass-radius) stable branch, re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…3, where we show the λa − λs correlation for the EoS and binary parameters used in this work. We can clearly see that, in line with Tan et al (2021), there is a bimodal scatter separating EoSs with backwards-and forwards-bending massradius curves. Because the binary-Love relation also depends on the neutron star radius and mass-radius slope, but with a different dependence than our two-parameter, quasi-universal relations for f 2 , combined detections of inspiral and post-merger should enable a reconstruction of the linearized mass-radius curve.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…3, where we show the λa − λs correlation for the EoS and binary parameters used in this work. We can clearly see that, in line with Tan et al (2021), there is a bimodal scatter separating EoSs with backwards-and forwards-bending massradius curves. Because the binary-Love relation also depends on the neutron star radius and mass-radius slope, but with a different dependence than our two-parameter, quasi-universal relations for f 2 , combined detections of inspiral and post-merger should enable a reconstruction of the linearized mass-radius curve.…”
Section: Resultssupporting
confidence: 77%
“…These relations relate symmetric, λs = 1 2 λ1 + λ2 , and antisymmetric, λa = 1 2 λ1 − λ2 , combinations of the mass-normalized tidal deformabilities λ1,2 of the inspiralling neutron stars in an EoS-insensitive way (Yagi & Yunes 2016). In a recent work, Tan et al (2021) showed that these relations, previously thought to be fully universal, also receive an effective correction that is linearly proportional to the slope of the mass-radius curve. We illustrate this behavior in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this possibility for the violation was soon also realized in non-holographic frameworks [285,286] as well. 8 See also the recent work [289], which studies generalizations of universal relations in binary systems in the presence of first order phase transitions.…”
Section: Lessons From the Deconfined Phasementioning
confidence: 99%
“…This allows to uniquely identify the differences and similarities in compression, temperature, entropy and isospin, as well as comparing carefully the dynamical evolution of the geometry of the two systems. In this way, we can map specific microscopic initial conditions in the laboratory to macroscopic mergers consistent with previous gravitational-wave events [1,2,12], and obtain information on the properties of compact stars, such as the maximum mass [13][14][15][16], or typical radii and tidal deformabilities [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%